Tuning anisotropies for dynamical gauge configurations - PEARDON, MICHAEL JAMES; RYAN, SINEAD MARIE (SISSA, 2005)
We present methods and results for the tuning of quark and gluon anisotropies for improved actions in Nf = 2 QCD.
PUBLISHED
Keywords: Pure & Applied Mathematics